ANALISIS MODEL DAN IDENTIFIKASI FAKTOR PENDUKUNG DAN PENGHAMBAT DALAM PROSES REKRUTMEN BAGI TENAGA KERJA PENYANDANG DISABILITAS FISIK DI KOTA SERANG - Melani Dwi Agustini; Arta Rusidarma Putra; Isnaini Mahuda (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The difficulty of people with disabilities in Serang City in getting a job both in government agencies and in private companies, even though the right to get a job has been supported by Law Regulation No. 13 of 2019. One of the causes is supporting factors and obstacles in the recruitment process that cause problems in the recruitment model of people with disabilities. The purpose of the study is to analyze recruitment models and identify supporting factors and inhibit the recruitment process of people with physical disabilities in Serang City. This research uses descriptive qualitative methods, data collection techniques using interviews, observations with relevant parties and document studies. The results of the study are that the recruitment model of people with disabilities is closely related to supporting factors in the recruitment process of prospective workers with disabilities including skills, relationships and education, while the inhibiting factors are lack of family support, self-spirit, accessibility and environment. The conclusion of this study is that there are several obstacles to the recruitment model, namely the availability of limited quality resources, low levels of education and knowledge and criteria that cannot be met by prospective employees who are closely related to supporting factors and obstacles in the recruitment process of prospective workers with physical disabilities in Serang City. The existence of inhibitory factors in the recruitment process resulted in supporting factors not running optimally, thus causing various obstacles in the existing recruitment model